2015
DOI: 10.1016/j.physa.2014.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Biophysics of protein–DNA interactions and chromosome organization

Abstract: The function of DNA in cells depends on its interactions with protein molecules, which recognize and act on base sequence patterns along the double helix. These notes aim to introduce basic polymer physics of DNA molecules, biophysics of protein-DNA interactions and their study in single-DNA experiments, and some aspects of large-scale chromosome structure. Mechanisms for control of chromosome topology will also be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 133 publications
3
80
0
Order By: Relevance
“…At low HU concentration, the bending rigidity of the DNA always is reduced irrespective of whether the HUinduced°exible hinges result in rigid bends. 14,16,18 At higher HU concentration, the spontaneous formation of HU¯laments due to DNA allostery creates large°exible hinges 4 ; however, their e®ectiveness is limited by the repulsive HU-HU electrostatic interaction. Electrostatic interactions increase the rigidity of the¯laments, which consequently increase the sti®ness of the DNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At low HU concentration, the bending rigidity of the DNA always is reduced irrespective of whether the HUinduced°exible hinges result in rigid bends. 14,16,18 At higher HU concentration, the spontaneous formation of HU¯laments due to DNA allostery creates large°exible hinges 4 ; however, their e®ectiveness is limited by the repulsive HU-HU electrostatic interaction. Electrostatic interactions increase the rigidity of the¯laments, which consequently increase the sti®ness of the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…13) to incorporate the e®ects of DNA bending or sti®ening proteins. [14][15][16] Through transfer matrix calculations, they provided the exact results of DNA end-to-end distributions and force-extension curves as a function of bending proteins concentration. They particularly showed that both thermally-induced and protein-induced local DNA inhomogeneities could facilitate the cyclization of short DNA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Although supercoiled DNA has been extensively studied theoretically (10)(11)(12)(13)(14)(15)(16)(17)(18) as well as experimentally (19)(20)(21)(22)(23)(24)(25)(26), both simulation and experimental studies that directly investigate the large-scale organization of supercoiled DNA are typically limited to supercoiling densities up to the average supercoiling density in E. coli (s~À0.06). However, the topological state of the bacterial chromosome is highly dynamic (27), and both DNA gyrase and RNA polymerase are capable of generating negative supercoiling densities far in excess of average supercoiling levels (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…Despite decades of theoretical and computational investigation on supercoiled DNA (10)(11)(12)(13)(14)(15)(16)(17)(18)(34)(35)(36), the behavior of supercoiled DNA rings in free solution at the length scale of topological domains in bacteria with supercoiling <s~À0.07 has remained underexplored. However, these larger linking deficits represent an important biological regime, because DNA gyrase is capable of generating supercoiling densities up to s~À0.12, and RNA polymerase has been observed to generate similar or greater linking deficits (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…L p has been measured using different methods in various conditions. The values can vary widely [32], but the consensus value for modeling purpose is around 50 nm [33]. …”
Section: Theorymentioning
confidence: 99%